Prognostic Factors and Treatment‐Effect Modifiers in Spinal Muscular Atrophy. Issue 6 (5th June 2021) - Baranello, Giovanni; Gorni, Ksenija; Daigl, Monica; Kotzeva, Anna; Evans, Rachel; Hawkins, Neil; Scott, David A.; Mahajan, Anadi; Muntoni, Francesco; Servais, Laurent
Abstract : Spinal muscular atrophy (SMA) is a rare, progressive neuromuscular disease characterized by loss of motor neurons and muscle atrophy. Untreated infants with type 1 SMA do not achieve major motor milestones, and death from respiratory failure typically occurs before 2 years of age. Individuals with types 2 and 3 SMA exhibit milder phenotypes and have better functional and survival outcomes. Herein, a systematic literature review was conducted to identify factors that influence the prognosis of types 1, 2, and 3 SMA. In untreated infants with type 1 SMA, absence of symptoms at birth, a later symptom onset, and a higher survival of motor neuron 2 ( SMN2 ) copy number are all associated with increased survival. Disease duration, age at treatment initiation, and, to a lesser extent, baseline function were identified as potential treatment‐modifying factors for survival, emphasizing that early treatment with disease‐modifying therapies (DMT) is essential in type 1 SMA. In patients with types 2 and 3 SMA, factors considered prognostic of changes in motor function were SMN2 copy number, age, and ambulatory status. Individuals aged 6–15 years were particularly vulnerable to developing complications (scoliosis and progressive joint contractures) which negatively influence functional outcomes and may also affect the therapeutic response in patients. Age at the time of treatment initiation emerged as a treatment‐effect modifier on the outcome of DMTs. Factors identified in this review should be considered prior to designing or analyzing studies in an SMA population, conducting population matching, or summarizing results from different studies on the treatments for SMA.